The Antioxidant Vitamin (A, C, E) and the Lipid Peroxidation Levels in Some Tissues of Juvenile Rainbow trout (Oncorhynchus mykiss, W. 1792) at Different Oxygen Levels. - Tuna Keleştemur, Gülüzar (My University, 2012)
In this study, the malondialdehyde (MDA) levels in the muscle, liver and kidney tissues and the antioxidant vitamin (A, C, E) levels in the muscle tissue of juvenile rainbow trout were investigated under different oxygen levels (3.5 mg O2/l, 4.5 mg O2/l and 7 mg O2/l) at the end of the 8 hour trial. Fish (initial weight and length, 30.19±2.2 g and 13.15±0.22 cm, respectively) were distributed into 9 fiberglass rectangular tanks. The highest MDA level of all tissues was obtained in 3.5 mg O2/l (p<0.05). Different oxygen levels did not affect muscle vitamin A concentration statically (p>0.05). But the highest muscle vitamin C and E concentrations were obtained in 7 mg O2/l. (p<0.05), followed by 3.5 mg O2/l, while the lowest muscle vitamin C concentration was obtained in 4.5 mg O2/l. (p<0.05).
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Rainbow trout; Hypoxia; Stress; Antioxidant vitamins; Lipid peroxidation; Tissue